Mir-4728 is a Valuable Biomarker for Diagnostic and Prognostic Assessment of HER2-Positive Breast Cancer - Rui, Tao; Xiang, Aizhai; Guo, Jufeng; Tang, Ning; Lin, Xia; Jin, Xin; Liu, Jian; Zhang, Xiaobing (Frontiers in Molecular Biosciences, 2022)
Breast cancer remains one of the most common malignancies in female cancer patients. The rapid and accurate diagnosis of Human Epidermal Growth Factor Receptor 2 (HER2) status is indispensable for breast cancer patients. The pre-miR-4728 (mir-4728) is encoded within an intron of the HER2 gene. We showed here that mir-4728 was the most significantly upregulated pre-miRNA in HER2-positive breast cancer patients (fold-change: 4.37), and it could serve as a strong diagnostic factor for HER2 status in breast cancer patients (P < 0.0001). Besides, mir-4728 was positively correlated with tumor recurrence and appeared to be a critical independent risk factor of tumor recurrence in patients with high tumor burden (HR: 7.558, 95% CI:1.842-31.006, P = 0.005). Remarkably, HER2-positive patients with higher mir-4728 expression levels had better drug responses to targeted therapies. Furthermore, Estrogen Receptor (ESR), the predictive marker for endocrine therapies, was found to be the direct target of miR-4728-3p. Taken together, our results supported a potential role of mir-4728 in the diagnosis of HER2 status and the prognostic assessment of HER2-positive breast cancer patients in response to targeted therapies.